A Time-Domain Artificial Boundary for Near-Field Wave Problem of Fluid Saturated Porous Media - Jia Song; Fujie Wang; Kemin Jia; Haohao Shen (Mathematical and Computational Applications, 2022)
The near-field wave problem of the saturated soil involves the energy radiation effect of the truncated infinite media. A viscous spring boundary is proposed for the fluid-saturated porous media. Based on the process of wave propagation under internal point source, the stress and flow velocity boundaries are constructed by reasonable assumptions of outgoing waves and Green’s function, respectively. Without the permeability assumption, the proposed boundary avoids the low accuracy caused by the assumption of zero permeability that is widely used in the existing methods. The boundary simultaneously has a simple form, clear physical meaning, and less computational cost due to its local character. Meanwhile, a completely explicit integration algorithm considering the damping is constructed to solve the finite element equations of saturated porous media with the proposed boundary. The accuracy and high computational efficiency of the wave numerical method are verified in the examples.